Ship Emission Impacts on Air Quality and Human Health in the Pearl River Delta (PRD) Region, China, in 2015, With Projections to 2030. Issue 9 (30th September 2019) - Chen, Chen; Saikawa, Eri; Comer, Bryan; Mao, Xiaoli; Rutherford, Dan
Abstract : Ship emissions contribute to air pollution, increasing the adverse health impacts on people living in coastal cities. We estimated the impacts caused by ship emissions, both on air quality and human health, in 2015 and future (2030) within the Pearl River Delta (PRD) region of China. In addition, we assessed the potential health benefits of implementing an Emission Control Area (ECA) in the region by predicting avoided premature mortality with and without an ECA. In 2015, ship emissions increased PM2.5 concentrations and O3 mixing ratios by 1.4 μg/m 3 and 1.9 ppb, respectively, within the PRD region. This resulted in 466 and 346 excess premature acute deaths from PM2.5 and O3, respectively. Premature mortality from chronic exposures was even more significant, with 2, 085 and 852 premature deaths from ship‐related PM2.5 and O3, respectively. In 2030, we projected the future ship emissions with and without an ECA, using two possible land scenarios. With an ECA, we predicted 76% reductions in SO2 and 13% reductions in NO x from the shipping sector. Assuming constant land emissions from 2015 in 2030 ( 2030 Constant scenario), we found that an ECA could avoid 811 PM2.5 ‐related and 108 O3 ‐related deaths from chronic exposures. Using 2030 Projected scenario for land emissions, we found that an ECA would avoid 1, 194 PM2.5 ‐related and 160 O3 ‐related premature deaths in 2030. In both scenarios, implementing an ECA resulted in 30% fewer PM2.5 ‐related premature deaths and 10% fewer O3 ‐related premature deaths, illustrating the importance of reducing ship emissions. Key Points: In 2015, ship emissions increased summer PM2.5 and O3 by 1.4 μg/m 3 and 1.9 ppb, respectively, within the Pearl River Delta (PRD), China Ship emissions caused over 2, 500 PM2.5 ‐related and 1, 200 O3 ‐related premature deaths in the PRD region in 2015 Implementing an Emission Control Area in the PRD region in 2030 could reduce mortality due to PM2.5 and O3 exposures by 30% and 10%, respectively